Unravelling the Portuguese Coastal and Transitional Waters’ Microbial Resistome as a Biomarker of Differential Anthropogenic Impact - Bernardo Duarte; Andreia Figueiredo; Patrício Ramalhosa; João Canning-Clode; Isabel Caçador; Vanessa F. Fonseca (Toxics, 2022)
Portugal mainland and Atlantic archipelagos (Madeira and Azores) provide a wide array of coastal ecosystems with varying typology and degrees of human pressure, which shape the microbial communities thriving in these habitats, leading to the development of microbial resistance traits. The samples collected on the Portuguese northeast Atlantic coast waters show an unequivocal prevalence of Bacteria over Archaea with a high prevalence of Proteobacteria, Cyanobacteria, Bacteroidetes and Actinobacteria. Several taxa, such as the Vibrio genus, showed significant correlations with anthropogenic pollution. These anthropogenic pressures, along with the differences in species diversity among the surveyed sites, lead to observed differences in the presence and resistance-related sequences’ abundance (set of all metal and antibiotic resistant genes and their precursors in pathogenic and non-pathogenic bacteria). Gene ontology terms such as antibiotic resistance, redox regulation and oxidative stress response were prevalent. A higher number of significant correlations were found between the abundance of resistance-related sequences and pollution, inorganic pressures and density of nearby population centres when compared to the number of significant correlations between taxa abundance at different phylogenetic levels and the same environmental traits. This points towards predominance of the environmental conditions over the sequence abundance rather than the taxa abundance. Our data suggest that the whole resistome profile can provide more relevant or integrative answers in terms of anthropogenic disturbance of the environment, either as a whole or grouped in gene ontology groups, appearing as a promising tool for impact assessment studies which, due to the ubiquity of the sequences across microbes, can be surveyed independently of the taxa present in the samples.